Upside-Down Gods : Gregory Bateson's World of Difference - Harries-Jones, Peter (Book collections on Project MUSE., 2016)
"This intellectual biography covers the whole trajectory of Bateson's career, from his first anthropological work alongside Margaret Mead through the continuing relevance of his late forays into biosemiotics. Harris-Jones shows how the sum of Bateson's thinking across numerous fields turns our notions of causality upside-down, providing a moral divide between sustainable creativity and our current biocide."